Answer:
B) 2x+3=4
Step-by-step explanation:
6x+9=12
6x=12-9
6x=3
x=3/6
x=1/2
---------------
Because 2x+3=4, 2x=4-3, 2x=1, x=1/2.
Resolving a function of any nature means determining your zeros or raizes.
The zeros of a function occur when the function is null.
Then:
f(x) = 3x - 2
To determine the root
f(x) = 0 = 3x - 2
3x = 2
x = 2/3 Final result
Answer:
y - 3= 2(x - 0)
Step-by-step explanation:
hello :
note 1 :
the point-slope formula is :
y - y_1 = m(x - x_1) the point is A(x_1 , y_1 ) , m : the slope
note 2 :
the slope is : m = (y_2 - y_1)/(x_2 -x_1) when given two points :
A(x_1 , y_1 ) and B(x_2 , y_2 )
in this exercice : x_1 =0 y_1 =3 x_2 =1 y_2 =1
calculate now m = (1 - 3)/(1 -0) =-2
an equation in point-slope form is : y - y_1 = m(x - x_1)
y - 3= 2(x - 0)
Answer: B is correct. Triangle PRS can be proven equilateral, and the hexagon is equilateral.
Step-by-step explanation: We can't see the theorem she applied however
From the construction, we can see that the arcs are drawn properly to construct an equilateral hexagon, and the component triangles are all equilateral
We know that
the transformation
f(x)--------> f(x+2)
that means
A point (x,y) in graph of f(x)------> become a point (x-2, y) in graph of f(x+2)
hence
point (5,-8)-------------> become a point (5-2,-8)-----> (3,-8)
the answer is
the point (3,-8)